ANALISIS SPIRITUALITAS PARA PENCARI BERKAH (Studi atas Motivasi Peziarah di Makam Sunan Kalijaga Kadilangu Demak) - Mustagfiroh, Hikmatul; Mustaqim, Muhamad (Jurnal Penelitian, 2014)
SPIRITUALITY ANALYSIS OF BLESSING SEEKERS (A STUDY ON THE MOTIVATION OF PILGRIMS AT THE GRAVE OF SUNAN KALIJAGA KADILANGU DEMAK). For the people of Islam-Java, pilgrimage to the religious leader grave is believed to be the religiuos tradition. Sunan Kalijaga was one of the Walisongo which the grave is in Kadilangu area, close to the complex of the great mosque of Demak. The pilgrims who visit the Kadilangu grave have some motivation behind the spirituality behavior of blessing seekers. This paper summarizes some of the motivation of the pilgrims at the grave of Sunan Kalijaga. Some of them are the motivations of religion, religious tourism, seeking blessings, wasilah in praying, tolak bala ‘, spiritual practice, and look for the crowd. So there are still many other motivations that haven’t been covered in this study.